ANTIOXIDANTS IN TREATMENT OF CHRONIC RENAL ALLOGRAFT DYSFUNCTION - R.O. Zograbian (Український Журнал Нефрології та Діалізу, 2014)
Treatment of chronic renal allograft dysfunction (CRAD) presents a serious challenge for modern transplantology, therefore clarifying the mechanisms of development and improving treatment modalities of this complication is of great importance.